The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fped.2020.00382
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Early Treatment With Chenodeoxycholic Acid in Cerebrotendinous Xanthomatosis Presenting as Neonatal Cholestasis

Abstract: Background: Cerebrotendinous xanthomatosis (CTX) is an inborn disorder of bile acid synthesis which causes progressive accumulation of toxic metabolites in various organs, particularly in brain and tendons. Most cases are diagnosed and treated in the second or third decade of life, when neurological involvement appears. We describe a case of CTX presenting as neonatal cholestasis. Results: The child presented cholestasis at 2 months of life. In the following months jaundice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Degrassi et al have recently reported a patient who started to be treated at 8 months of age with the initial dose of 10 mg/kg/day, increased until 15 mg/kg/day. The patient has been followed for 13 years and the therapy was well-tolerated ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Degrassi et al have recently reported a patient who started to be treated at 8 months of age with the initial dose of 10 mg/kg/day, increased until 15 mg/kg/day. The patient has been followed for 13 years and the therapy was well-tolerated ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective analysis of the past medical records of 50 Dutch patients with CTX, authored by Clayton et al, revealed that neonatal liver disease defined as prolonged jaundice with raised serum transaminases occurred much more often in CTX than in the general population (13). Up to now, neonatal cholestatic jaundice in the course of CTX has been reported in 14 patients, in most of them presenting as a selflimiting disease (11)(12)(13)(14)(15)(16)(17)(18)(19). However, a fatal neonatal cholestasis has been reported in 5 out of 12 patients (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chenodeoxycholic acid is the current standard of therapy. 35 With treatment started early, the improvement in patients can be remarkable. 35,202 Unfortunately, treatment initiated too late can bring no favorable effects.…”
Section: Treatmentmentioning
confidence: 99%
“…4 CTX patients present complex and heteroge-neous clinical manifestations, including chronic diarrhea with infantile onset, juvenile cataracts, tendon xanthomas, osteoporosis, premature atherosclerosis, mild respiratory insufficiency, and progressive neuropsychiatric alterations (ataxia, peripheral neuropathy, epilepsy, depression, and cognitive deterioration). 5 Some reports describe cases of severe infantile cholestasis, [6][7][8] although liver damage is not a common characteristic of this disease. The onset and severity of symptoms differ among CTX patients, which contributes to the fact that their diagnosis is usually delayed more than 15 years.…”
Section: Introductionmentioning
confidence: 99%